The impact of Lactococcus lactis (probiotic nasal rinse) co‐culture on growth of patient‐derived strains of Pseudomonas aeruginosa. Issue 4 (10th January 2020) - Cho, Do‐Yeon; Skinner, Daniel; Lim, Dong Jin; Mclemore, John G.; Koch, Connor G; Zhang, Shaoyan; Swords, William E.; Hunter, Ryan; Crossman, David K; Crowley, Michael R.; Grayson, Jessica W.; Rowe, Steven M.; et al.
Abstract : Background: The Lactococcus strain of bacteria has been introduced as a probiotic nasal rinse for alleged salubrious effects on the sinonasal bacterial microbiome. However, data regarding interactions with pathogenic bacteria within the sinuses are lacking. The purpose of this study is to assess the interaction between L. lactis and patient‐derived Pseudomonas aeruginosa, an opportunistic pathogen in recalcitrant chronic rhinosinusitis (CRS). Methods: Commercially available probiotic suspension containing L. lactis W136 was grown in an anaerobic chamber and colonies were isolated. Colonies were co‐cultured with patient‐derived P. aeruginosa strains in the presence of porcine gastric mucin (mimicking human mucus) for 72 hours. P. aeruginosa cultures without L. lactis served as controls. Colony forming units (CFUs) were compared. Results: Six P. aeruginosa isolates collected from 5 CRS patients (3 isolates from cystic fibrosis [CF], 1 mucoid strain) and laboratory strain PAO1 were co‐cultured with L. lactis . There was no statistical difference in CFUs of 5 P. aeruginosa isolates grown with L. lactis compared to CFUs without presence of L. lactis . CFU counts were much higher when the mucoid strain was co‐cultured with L. lactis (CFU +L.lactis = 1.9 × 108 ± 1.44 × 107, CFU –L.lactis = 1.3 × 108 ± 8.9 × 106, p = 0.01, n = 7). L. lactis suppressed the growth of 1 P. aeruginosa strain (CFU +L.lactis = 2.15 × 108 ± 2.9 × 107, CFU –L.lactis = 3.95 × 108 ± 4.8 × 106, p = 0.03, n = 7). Conclusion: L. lactis suppressed the growth of 1 patient P. aeruginosa isolate and induced growth of another (a mucoid strain) in in vitro co‐culture setting in the presence of mucin. Further experiments are required to assess the underlying interactions between L. lactis and P. aeruginosa .